دل کے روحانی امراض کےاثرات ونقصانات: تدارک قرآن وسنت کی روشنی میں: Effects and damages of spiritual diseases of the heart: Remedy in the light of Quran and Sunnah - Dr. Haq Nawaz; Ameer Maviya; Abubakar Siddique (International Research Journal of Arabic and Islamic Studies, 2024)
Man is a combination of body and soul. Just as the heart is of great importance from the physical point of view, the heart is also very important from the spiritual point of view, just as the heart can be sick and healthy from the physical point of view, similarly the heart from the spiritual point of view can be both sick and healthy. Nowadays, even heart diseases are not paid attention to, which is the great tragedy of this age. Doubts and whispers in heart diseases are diseases that do not allow a person to remain calm. For which it is necessary that a person continues to organize prayers. Hardness of heart is a great spiritual disease due to which the man becomes oblivious to the remembrance of Allah. Hearts also get rusty, which is a sign of misguidance, the main reason for this is the abundance of sins. Hypocrisy is a great disease, which is the cause of waste of actions, to avoid it, it is necessary to correct the intention. Negative thinking creates mistrust in a person, which is prohibited by Shariat. Greed and greed never make a person happy, this greed is the cause of death. Only by avoiding all these diseases can a person become an important and useful part of society, can also become a good person and can also become a good Muslim.